Mathematics & Science Education and Income: An Empirical Study in Japan - Hirata, Junichi; Nishimura, Kazuo; Urasaka, Junko; Yagi, Tadashi (Journal of Reviews on Global Economics, 2013)
Abstract: Since the second half of the 1990s, the decline in academic standards in mathematics and science among undergraduate students in Japan has been noted. Despite this, problems in science education have become increasingly severe, and their impact is having a mounting effect on Japan's economy. This paper studies the return to a university education in Japan by taking into account the relative ranking of the universities. We present an empirical analysis of how annual income differs depending on whether a major is natural science or humanities. We have found that science graduates have a higher average income than humanities graduates indicates that the added value they are producing is higher than that of humanities graduates. Of particular interest is the fact that a comparison of humanities graduates of A rank universities who did not sit admission examinations in mathematics with science graduates of B rank university showed that it was the science graduates who recorded higher average income at every age grade. The above comparison also reveals that even those humanities graduates of A rank universities who did sit admission examinations in mathematics are out-earned by science graduates of B rank universities in the under 30 and 55 and over age groups.